Textualidades da composição: instâncias escritas no processo tradutório da canção contemporânea - Adeodato Júnior, Jorge Luiz (2019)
In this work I will address the multiple forms on which "song", as part of the poetic genre, presents itself in our time. understanding,. My approach to the subject is to consider “song” “oral poetry” in the way defined by Paul Zumthor’s in his 1983 homonimous introduction to the topic,. From that point on, I shall frame the current work of contemporary songwriting as a construct of an oral lyricism, emphasizing its characteristics through: a) constant dialogues in a tradition that is twofold: musical and literary; b) ingenious use of figures of language and narrative when constructing metaphoric imagery; c) a constant revision and reformulation of its precepts through transgressions that, in a gradual and progressive manner, conduct the genre ahead. Fully aware that my focus is on an artistic and discursive instance very close to what is commonly known as mass culture, I shall also discuss, along with Zumthor (1993; 2007; 2010), Benjamin (1999) and cultural critics such as Marshall McLuhan (1994) and Greil Marcus (2001; 2006; 2009) ways of connecting the numerous pieces in which a song can present itself to a reader / listener, in order to get a broader picture of it as a "text". I shall take into account both the audio of the official studio recordings and what is possible to comprehend as "the printed word" — either as a book or other sources, such as inserts and booklets that function as a written support to the audio material. I will then analyze the output of songwriters whose lyrics were recently collected and published in book form: Bob Dylan (2017) and Nick Cave (2013, still unpublished in Portuguese at the time of writing of this dissertation). From a multidimensional comprehension of what can be understood as text, I will propose a reflection on how songs can be properly read as source material in the translation process, so that versions truer to the particularities of the source text may be achieved.